2016
DOI: 10.1080/19336918.2016.1212139
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic fragments of fibronectin function as matrikines driving the chemotactic affinity of prostate cancer cells to human bone marrow mesenchymal stromal cells via the α5β1 integrin

Abstract: The haematopoietic niche is contributed to by bone marrow-resident mesenchymal stromal cells (BM-MSCs) and subverted by prostate cancer cells. To study mechanisms by which BM-MSCs and prostate cancer cells may interact, we assessed the migration, invasion, adhesion and proliferation of bone-derived prostate cancer cells (PC-3) in co-culture with pluripotent human BM-MSCs. We observed a strong adhesive, migratory and invasive phenotype of PC-3 cells with BM-MSC-coculture and set out to isolate and characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…Another recent study indicated that the dysregulated of FN1 restricted prostate cancer cell invasion [12]. And the enhanced fibronectin expression in tamoxifen-resistant breast cancer cells had been reported by You et al [13].…”
Section: Introductionmentioning
confidence: 79%
“…Another recent study indicated that the dysregulated of FN1 restricted prostate cancer cell invasion [12]. And the enhanced fibronectin expression in tamoxifen-resistant breast cancer cells had been reported by You et al [13].…”
Section: Introductionmentioning
confidence: 79%
“…However, similar results to ours were found in a study, which showed that proliferation could not be induced in rat‐derived bone marrow mesenchymal stem cells treated with 0.1–100 μg/ml pFN (Jimbo et al, ). The same was observed in prostate cancer cells, where FN did not show a stimulating effect on cell proliferation (Joshi, Goihberg, Ren, Pilichowska, Mathew, ).…”
Section: Discussionsupporting
confidence: 62%
“…LLC formation enables spatio‐temporal regulation of interaction of TGF‐beta with cell surface receptors which is prevented by LLCs and is enabled by local proteolytic cleavage of ECM. Furthermore, proteins of ECM possess elements which are released by proteolysis and activate matrikines signaling by binding to cell surface receptors (as shown for fibronectin producing a rise of matrikines which in turn promote cell motility). Testing this hypothesis would require focused perinodal knockdown of ECM‐related NMC components to minimize global deleterious effects even if this may be challenging in view of the dynamic character of the node .…”
Section: Discussionmentioning
confidence: 99%